SISTEM APLIKASI UNTUK KEAMANAN DATA DENGAN ALGORITMA 'DES' (Data Encryption Standard) - Dadang Priyanto; Raisul Azhar (Universitas Bumigora, 2016)
Data is very important its existence to be protected if the data has a value, or a specific confidentiality. There are so many techniques that can be used to secure the data, one is to apply the method Encryption and Decryption. In the Encryption Method and Description using various types of algorithms. Applications built using algorithms Encription Data Standard (DES). This algorithm emphasizes on input (plaintext) whose length is 64 bits and a key length of 56 bits, and through 16 stages or iterations. Results from making this application can be used to encrypt all files except the video. This application has an encryption rate of 3 sec / each file capacity of 1024 bytes. The rate of speed encryption and decryption with polygons forming linear graph is a straight line.